2017
DOI: 10.1038/eye.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes to the retina and optic nerve following panretinal photocoagulation over a 2-year time period

Abstract: PurposeTo evaluate long-term structural and functional changes to the retina and optic nerve following panretinal photocoagulation (PRP) in diabetic retinopathy (DR) patients.MethodsParticipants were patients with DR requiring PRP and control patients with DR not requiring PRP. The Heidelberg retinal tomography (HRT) and optical coherence tomography (OCT) were performed to analyze the optic nerve and macula. Best-corrected visual acuity (BCVA) and visual field (VF) testing were done to measure central and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Over the long-term followup, they gradually returned to the baseline level. Many of the previous studies using OCT obtained similar results (27,28). They considered that the retinal inflammation and edema caused by PRP at the early postoperative phase could damage the retinal neural cell and tissue and later recovery might be attributed to the absorption and healing of the edema and the laser-induced photoreceptors and ganglion cell damage.…”
Section: Discussionmentioning
confidence: 75%
“…Over the long-term followup, they gradually returned to the baseline level. Many of the previous studies using OCT obtained similar results (27,28). They considered that the retinal inflammation and edema caused by PRP at the early postoperative phase could damage the retinal neural cell and tissue and later recovery might be attributed to the absorption and healing of the edema and the laser-induced photoreceptors and ganglion cell damage.…”
Section: Discussionmentioning
confidence: 75%
“…In a study with a small population (10 eyes), there were no negative effects of treatment regarding VF in the short term (6 months). 7 On the other hand, in a recent prospective 2-year study, Filek et al 17 described a significant loss in VF evaluation in 16 patients undergoing PRP. In the scientific literature, no studies comprising long-term results in a large sample were found, as in the present study.…”
Section: Discussionmentioning
confidence: 99%